Sulfur-Mediated Polycarbonate Polyurethane for Potential Application of Blood-Contacting Materials - Li, Peichuang; Cai, Wanhao; Li, Xin; Zhang, Hong; Zhao, Yuancong; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, a sulfur-mediated polycarbonate-polyurethane (PCU-SS) is developed by mimicking the catalyze ability of glutathione peroxidase (GPx) on nitric oxide (NO) in the human body. The PCU-SS is endowed with capability to produce NO based on the disulfide bonds, which could strongly improve the biocompatibility of the materials. The characterization results indicate that PCU-SS could not only decrease the adhesion of platelets, but also enhance the capability of anti-thrombus. Moreover, it is shown that PCU-SS has good compatibility with endothelial cell (EC), while has marked inhibition capacity of the proliferation of smooth muscle cell (SMC) and macrophage (MA). Meanwhile, the result of animal implantation experiments further demonstrates the good abilities of PCU-SS on anti-inflammation, anti-thrombus, and anti-hyperplasia. Our results offer a novel strategy for the modification of blood-contacting materials based on disulfide bonds. It is expected that the PCU-SS could bring new light for biocompatibility improvement of cardiovascular stents.